1991
DOI: 10.1111/j.1365-3032.1991.tb00538.x
|View full text |Cite
|
Sign up to set email alerts
|

Response specificity of male olfactory receptor neurones for the major and minor components of a female pheromone blend

Abstract: The sex attractant of the female redbanded leafroller moth, Argyrotaenia velutinana (Walker), is a blend of seven compounds. Specialized olfactory receptor neurones had been found for only two of the compounds, (Z)‐11‐tetradecenyl acetate (Z11‐14:Ac) and (E)‐11‐tetradecenyl acetate (E11–14:Ac). These receptor neurones were always found in pairs within the long trichoid sensilla, which are the most abundant multi‐pored sensilla on the male antenna. A systematic survey of all regions of the male antenna with sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
(40 reference statements)
0
7
1
Order By: Relevance
“…A major part of the peripheral coding system for the two principal pheromone components resides in neurons responding to both of these components. This condition contrasts with previous studies stating that insect pheromone receptor neurons are highly specific in their response spectrum (Van der Pers and T. Takanashi and others Den Otter, 1978;Liljefors et al, 1987;Akers and O'Connell, 1991;Hansson et al, 1995;Mustaparta, 1997;Wojtasek et al, 1998;Kalinová et al, 2001;Larsson et al, 2002). This has been demonstrated in the closely related European corn borer, O. nubilalis Hansson et al, 1994;Cossé et al, 1995).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…A major part of the peripheral coding system for the two principal pheromone components resides in neurons responding to both of these components. This condition contrasts with previous studies stating that insect pheromone receptor neurons are highly specific in their response spectrum (Van der Pers and T. Takanashi and others Den Otter, 1978;Liljefors et al, 1987;Akers and O'Connell, 1991;Hansson et al, 1995;Mustaparta, 1997;Wojtasek et al, 1998;Kalinová et al, 2001;Larsson et al, 2002). This has been demonstrated in the closely related European corn borer, O. nubilalis Hansson et al, 1994;Cossé et al, 1995).…”
Section: Discussioncontrasting
confidence: 52%
“…furnacalis has a peculiar coding system for its two major pheromone components, whereas the close relative O. nubilalis has specialized neurons tuned to each pheromone component, as reported in many other moth species Akers and O'Connell, 1991;Mustaparta, 1997;Kalinová et al, 2001;Larsson et al, 2002). In rare cases, males of O. nubilalis show behavioral response to E12-and Z12-14:OAc (Roelofs et al, 2002;Linn et al, 2003), suggesting that their neurons can sometimes respond to the compounds of O. furnacalis.…”
Section: Discussionmentioning
confidence: 95%
“…Such male-specific trichoid sensilla have been observed in a number of moth species such as the redbanded leafroller, Argyrotaenia velutinana (Walker) (Lepidoptera: Tortricidae) and the corn earworm, Helicoverpa zea (Boddie) (Lepidoptera: Noctuidae) (Akers & O'Connell 1991;Cossé et al 1998). Electrophysiological recordings indicated that these male-specific trichoid sensilla in moths contained ORNs responsive to conspecific female sex pheromones and related compounds (Akers & O'Connell 1991;Cossé et al 1998). Therefore, it is likely that the ORNs in the male-specific trichoid sensilla are responsible for detecting the female sex pheromone and related compounds in P. xylostella.…”
mentioning
confidence: 99%
“…The study of how olfactory sensory neurons respond to stimuli presents a special challenge in honey bees compared with a number of species of moths (eg Kaissling and Priesner, 1970; Der Pers and Den Otter, 1978;Grant and O'Connell, 1986;van Der Pers and Löfstedt, 1986; Kaissling et al, 1989; Akers and O'Connell, 1991), beetles (Boeckh, 1962;Tommeras et al, 1984; De Jong and Visser, 1988), and cockroaches (Sass, 1978;Selzer, 1984;Fujimura et al, 1991), among others. In these latter organisms, (fig 1), and the firing rate of individual sensory neurons can only be extracted using computationally-based spike-sorting techniques.…”
Section: Introductionmentioning
confidence: 99%